2008
DOI: 10.3382/ps.2007-00417
|View full text |Cite
|
Sign up to set email alerts
|

Different Contamination Patterns of Lineage I and II Strains of Listeria monocytogenes in a Spanish Broiler Abattoir

Abstract: The purpose of this study was to determine whether genetically similar or diverse strains of Listeria monocytogenes colonize the environment and carcasses in a single Spanish broiler abattoir over time. The study was composed of 5 surveys over a 1.5-yr period and included the monitoring of cleaning and disinfection procedures. Overall, a total of 212 samples were tested for the presence of L. monocytogenes, and 31% of the samples were found to be positive. Listeria monocytogenes was isolated from carcasses and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 45 publications
1
19
0
1
Order By: Relevance
“…Persistence may indicate deficiencies in sanitation procedures or potential niches in the processing environment where L. monocytogenes is protected from sanitation. While persistence of L. monocytogenes in meat processing plants (15,37,38,61) and in other plants (44,47,73) has previously been reported, identification of different PFGE types (as well as different molecular serotypes and lineages) associated with persistence in different plants (except for one PFGE type associated with persistence in two plants) clearly suggests that many different L. monocytogenes strains have the ability to establish persistent populations in processing plants.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Persistence may indicate deficiencies in sanitation procedures or potential niches in the processing environment where L. monocytogenes is protected from sanitation. While persistence of L. monocytogenes in meat processing plants (15,37,38,61) and in other plants (44,47,73) has previously been reported, identification of different PFGE types (as well as different molecular serotypes and lineages) associated with persistence in different plants (except for one PFGE type associated with persistence in two plants) clearly suggests that many different L. monocytogenes strains have the ability to establish persistent populations in processing plants.…”
Section: Discussionmentioning
confidence: 90%
“…While L. monocytogenes persistence in food processing plants and other food-associated environments has been well documented (30,33,37,38,44,47), it still remains largely unclear whether persistent strains share unique genetic or phenotypic characteristics or whether establishment of persistence is largely a random process with most L. monocytogenes strains being able to establish persistence if they are introduced into an appropriate location at an opportune time. While some authors have reported that isolates representing persistent subtypes appear to possess specific characteristics that facilitate persistence, such as resistance to disinfectants (1,39), improved ability to adhere to food contact surfaces and to form biofilms (6,40), others have found no evidence that persistent strains adhere better to surfaces (28) or are more resistant to disinfectants (14,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Spain, López et al [6] detected a 31% occurrence of L. monocytogenes in chicken carcasses during the processing stages.…”
Section: Discussionmentioning
confidence: 99%
“…The contamination level by degrading and pathogenic indicator microorganisms, such as Salmonella spp. and Listeria monocytogenes is still a fact that should be set right in broiler abattoirs and in selling outlets where these products and their derivatives are commercialized [6,7,8].…”
Section: Introductionmentioning
confidence: 99%